1987
DOI: 10.1111/j.1600-0897.1987.tb00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Defined Phenotypes of Peripheral Blood Lymphocytes in Cancer of the Uterine Cervix

Abstract: Immunological phenotypes of lymphocytes from peripheral blood of 100 patients with different stages and histologies of cancer of the uterine cervix were analyzed using monoclonal antibodies and F(ab)2 fragments of antihuman immunoglobulin. The T lymphocyte population was decreased in advanced cases of the cancer along with a rise in the B cell numbers. The OKT4+ cells generally showed a decrease in the cancer patients in contrast to the increase shown by the OKT8+ cells. The OKT4/OKT8 ratio was altered in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In patients with advanced cervical carcinoma, depressed systemic immune responses have been observed. [1][2][3] Because human cervical carcinoma has a characteristic stepwise progression, the anticancer immune reactions are especially important for localizing the spread of this malignancy. 4,5 Various immune escape mechanisms of cancer have been proposed.…”
mentioning
confidence: 99%
“…In patients with advanced cervical carcinoma, depressed systemic immune responses have been observed. [1][2][3] Because human cervical carcinoma has a characteristic stepwise progression, the anticancer immune reactions are especially important for localizing the spread of this malignancy. 4,5 Various immune escape mechanisms of cancer have been proposed.…”
mentioning
confidence: 99%
“…Moreovcr, thc former group also fail to reattain pretreatment levels. We have shown previously the importance of immune function in malignant ccrvical neoplasia (Radhakrishna Pillai et al 1987, 1988a, 19886, 1990Balaram el al. 1988) and how it corresponded with the course of disease.…”
Section: Discussionmentioning
confidence: 91%
“…Blood was collected from each patient and control subject by venepuncture into sterile heparinized tubes, Blood samples were taken before radiotherapy, immediately after treatment, and then at intervals of 3 months. Lymphocytes were isolated using the method of Boyum (1968) and standardized by us (Radhakrishna Pillai et al 1987).…”
Section: Suppressor Cell Activitymentioning
confidence: 99%
“…A subsequent study, confined to patients with invasive cancer, found decreased CD4/CD8 ratios due to increased CD8 cell counts only at stage IIB or higher. Absolute B cell counts were increased concomitantly (Pillai et al, 1987). To conclude, although there is strong evidence for IS monitoring in CIN and invasive cervical cancer, there is a lack of longitudinal studies as well as a lack of consistency of the onset and progression of these IS changes over the disease spectrum.…”
Section: Bioimmunological Aspectsmentioning
confidence: 88%